2019
DOI: 10.33899/mmed.2019.161285
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vitamin C on the Structural Changes of Male Albino Rats Kidney Induced by Tramadol

Abstract: Aim of study: The aim of this work is to detect the toxic effects of tramadol on the microscopic structure of the kidneys of adult male albino rats, and the possible protective role of vitamin C against these toxic effects. Method: Thirty adult albino rats are used in this study. The animals were divided into three equal groups: Group A (control group): Animals were injected daily with normal saline for 4 weeks. Group B (Tramadol treated group) (TGI): Animals were injected daily with tramadol in a dose of 50mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Oxidative damage is initiated by imbalance between oxidant and antioxidant resulting in mitochondrial damage and DNA damage which are the main manifestation of oxidative stress that occurs in cadmium toxicity [14], [15]. Concomtant use of antioxidants produce improvement in the histological structure of the organ, this finding is in agreement with the finding of other workers [16], [17], [18], [19], [20].…”
Section: Discussionsupporting
confidence: 86%
“…Oxidative damage is initiated by imbalance between oxidant and antioxidant resulting in mitochondrial damage and DNA damage which are the main manifestation of oxidative stress that occurs in cadmium toxicity [14], [15]. Concomtant use of antioxidants produce improvement in the histological structure of the organ, this finding is in agreement with the finding of other workers [16], [17], [18], [19], [20].…”
Section: Discussionsupporting
confidence: 86%
“…The animals which received cefotaxime I.P. with Vitamin C in the third group the hepato-renal changes were seem ameliorated than the second group, the liver cells appeared with less cytoplasmic vacuolation, absence of necrosis, and decreased the congestion and sinusoidal dilation but the inflammatory cells infiltration is still identified in some focal areas while the renal tissue shows normal appearing glomeruli and the eosinophilic material deposition on the bowman capsule was disappeared, the renal tubular epithelium with less degenerative features apart from still inflammatory cells infiltration, these changes were declare the effect of Vitamin C as protective agent against the injurious effects of cefotaxime that shown in the second group, which was proved by other study that shown the hepato-renal protective effects of Vitamin C after using the ceftriaxone [19], [20] and others when used Vitamin C as protective agents against the effect of some drugs or toxic agents [12], [13], [21].…”
Section: Discussionmentioning
confidence: 59%
“…Vitamin C is a water soluble vitamin which acts as antioxidant that can be used to ameliorate the hepato-renal toxicity induced by different agents [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…Co.). The chemical analysis of the pellets [9] showed that they contained 15.8 % crude protein, 11.3 % crude fibre, 3.7 % ether extract, 7.2 % ash, 92.9 % organic matter and 62.4 % nitrogen free extract % as DM basis.The first group was used as control, while, groups 2 was treated with tramadol by gavage at a dose of 50 mg/kg B.W/day (1/50 of tramadol) lethal dose [10]. for 6 successive weeks.…”
Section: Animals and Treatmentsmentioning
confidence: 99%